Image Encryption Using Image Division and Suffling Technique - Kumar Saw, Abhishek; Rathore, Yogesh Kumar (International Journal of Computer Sciences and Engineering, 2019)
Encryption is the most effective way to achieve data security and converting data to an unrecognizable or encrypted form. Its wide used to secure data sent over wireless networks and the internet. This paper aims at improving the protection and efficiency of image cryptography by employing a highly efficient shuffle based encryption rule and a comparable decryption rule supported random values obtained by using pseudo random number generator .In this paper, a image encryption is projected which has pixels shuffling image division technique. The planned algorithmic program has been examined using multiple analysis ways in and a PSNR value obtained is more than 35 in all cases which shows a good decryption.